Integrasi Building Information Modeling (BIM) terhadap Kesiapan Lulusan Teknik Sipil Menghadapi Transformasi Digital di Industri Konstruksi - Setiyono; Rahardianto, Trias (Journal of Practice Learning and Educational Development, 2024)
The development of digital technology has transformed the landscape of the construction industry, and one of the most important innovations in recent years is the implementation of Building Information Modeling (BIM). BIM provides solutions to enhance efficiency in the design, construction, and management of construction projects. This research explores the impact of integrating BIM into the civil engineering curriculum on students' readiness to face the challenges of an increasingly digitized construction industry. Through a quantitative and qualitative approach, this research uses pre-test and post-test to measure changes in students' competencies in using BIM after participating in the training. Three groups of civil engineering students were tested to measure their level of understanding before and after the BIM training. The research results show a significantincrease in post-test scores compared to pre-test scores in all three groups, with an average improvement of 24.7%. These results indicate that the integration of BIM in education can be effective in enhancing students' professional readiness and bridgingthe gap between academic theory and the practical demands of the modern construction industry. This study suggests that BIM should be more widely integrated into the civil engineering curriculum to prepare graduates who are ready to compete in the era of construction industry digitalization.